Pemberdayaan Masyarakat Berbasis Agropreneur dalam Mengatasi Pengangguran di Desa Gerupuk Kabupaten Lombok Tengah - Mariatun, Baiq; Rizka, Muhammad Arief (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2019)
The aimed of this study was to describe the implementation of an agropreneur-based community empowerment program through training in snapper cultivation in Gerupuk village. The research method used is descriptive method with a qualitative approach. The data sources of this study include program managers, instructors, and citizens of learning. The instrument of this study was the researchers themselves with the help of interview, observation, and documentation guidelines. Analysis of the data in this study used qualitative data analysis techniques with interactive models. The results of this study indicate that implementing an agropreneur-based community empowerment program through entrepreneurship training in snapper fish in Gerupuk village has been well implemented and in accordance with the principle of participatory empowerment. The stages of program management include planning, organizing, implementing, monitoring, and evaluating programs. The results of the program, namely the learning community can apply their knowledge to entrepreneurship in groups which has implications for improving the standard of living.